The Mubadalah Approach to Parental Rights and Obligations in Childcare According to Islamic Law - Multazam, Umar; Badrus Zaman, Akhmad Roja (Journal of Mujaddid Nusantara, 2024)
The present article elucidates the concept of child custody through the lens of the Mubadalah approach. The family serves as the primary environment for children from birth, where they acquire numerous life skills. Therefore, the dynamics of child custody, whether involving the father, the mother, or both parents equally, significantly impact the child’s cognitive, affective, and psychomotor development. This study aims to examine child custody as analyzed through the Mubadalah perspective. The research employs a qualitative methodology, specifically library research. The study involves a thorough review of literature pertaining to the Mubadalah approach as discussed in the book “Qiro’ah Mubadalah.” Data collection is executed through documentation, and the research process incorporates triangulation by comparing information from diverse theoretical perspectives found in various sources. The approach intertwines with data collection and encompasses data reduction, data presentation, and the formulation of conclusions. Findings from this research indicate that the Mubadalah approach to child custody is applicable and beneficial in childcare. It plays a crucial role in shaping children’s future personalities and characters, fostering a perspective of equality. The analytical concept of child care, as applied here, portrays a collaborative process between the father and mother, emphasizing shared responsibility and eliminating disparities in caregiving roles.